Internationalizing peace psychology - Christie, Daniel J.; Noor, Noraini M. (Springer, 2012)
In this chapter, we describe the history, growth, and current scope of peace psychology. We demonstrate how peace psychology has been dominated by the security concerns of Western countries. Then we ask the question: How would the current content and scope of peace psychology be changed if greater weight were given to the geohistorical issues, perspectives, and research agendas of scholars from Asia and developing parts of the world? We suggest that such an accommodation would require Western models of peace psychology to place greater emphasis on structural violence and the pursuit of social justice. In addition, Western models would need to be reconceptualized to include the role of personal peace and religion in the pursuit of intergroup peace and social justice. We conclude with a discussion of future research in peace psychology, focusing mostly on the importance of increasing contact and cooperation between the West and the rest of the world, to deal effectively with a range of conflicts including the global problem of ideological extremism.